(Mis)understanding American federalism: on constitutions, collective action, competition, and quiescence - Miller, L (2012)
American federalism is often lauded for promoting democratic participation and accountability, but this view neglects the ways in which it actually structures day-to-day political activity. Drawing on the concept of federalization of law and policy, this policy brief illustrates how lawmaking has proliferated across legal and legislative venues, particularly in the post-WWII period. Contrary to conventional wisdom, the author argues that the federalization of law and policy undermines the capacity of the public to act collectively, limits the ability of large groups of ordinary people to mount credible challenges to the status quo, and imposes obstacles to popular sovereignty over national lawmaking.